Effects of age and height portion on the chemical properties of Buluh Semantan (Gigantochloa scortechinii) / Jamaludin Kasim, Abd Jalil Ahmad and Abd Latif Mohmod - Kasim, Jamaludin; Ahmad, Abd Jalil; Mohmod, Abd Latif (Universiti Teknologi MARA Cawangan Pahang, 2000)
Cold water, hot water and alkali solubles content were significantly affected by age and height portion. Highest cold water (8.02%) and hot water (10.19%) content were observed in the top portion of two-year-old culm. They were found to have positive correlation with age and height portion. The top portion of three-year-old culm had the highest alkali solubles (25.52%) content and was shown to increased significantly with age and height portion. The alcohol benzenes solubles, ash and lignin content were not significantly affected by age and height portion. Holocellulose content increased significantly with age but remained almost constant with height portion.